150 Muscle Quantity at C3 And/or L3 on Routine Trauma Series Computed Tomography Correlate with Brain Frailty and Clinical Frailty Scale: A Cross-Sectional Study. (28th February 2022) - Gomindes, A.; Welch, C.; Chugh, R.; Appleton, J.
Abstract: Background: Sarcopenia is increasingly recognised to impact the quality of life and patient outcomes. The relationship with brain frailty is unknown. Objectives: Assess if muscle mass at C3 correlates with muscle mass at L3 on routine trauma imaging. Assess for associations between muscle-mass, brain-frailty, and Clinical Frailty Scale (CFS) on routine trauma imaging. Method: Routine trauma-series CT scans were retrospectively analysed for patients aged ≥16-years-old admitted to Queen-Elizabeth-Hospital in January2020. Paravertebral, sternocleidomastoid, and total muscle cross-sectional-area (CSA) at C3 (C3-SMM), and total psoas muscle CSA (TPA), total muscle CSA (L3-SMM), and total adipose CSA at L3 were calculated. Brain-frailty scores were calculated assessing for leukoaraiosis, cerebral atrophy, and old vascular lesions/infarcts. CFS was calculated retrospectively from clinical notes. We assessed for correlation against age, CFS, muscle-mass, and brain-frailty using Pearson's correlations. Results: We included 111 patients in this study (mean age 49, SD 25.6; 65.8% female). C3-SMM strongly correlated with L3-SMM (r=0.746, p<0.001). Paravertebral and sternocleidomastoid CSA correlated with C3-SMM (paravertebral: r=0.814, p<0.001; sternocleidomastoid: r=0.814, p<0.001). TPA strongly correlated with L3- SMM (r=0.800, p<0.001). Sternocleidomastoid CSA and TPA both negatively correlated moderately with age (sternocleidomastoid: r=−0.460, p<0.001; TPA: r=−0.468, p<0.001), CFS (sternocleidomastoid: r=−0.414, p<0.001; TPA: r=−0.431, p<0.001), and brain frailty (sternocleidomastoid: r=−0.395, p<0.001; TPA: r=−0.436, p<0.001). Adipose CSA at L3 did not correlate with age, CFS, brain-frailty, or muscle-mass. Conclusions: Muscle-mass at C3 relates to muscle-mass at L3. Muscle-mass on routine trauma-imaging is negatively associated with age, CFS, and brain-frailty.